Aligning the planets: The role of nurses in the care of patients with non‐ST elevation myocardial infarction. Issue 1 (4th November 2016) - Deaton, Christi; Johnson, Rachel; Evans, Maggie; Timmis, Adam; Zaman, Justin; Hemingway, Harry; Hughes, Jacqueline; Feder, Gene; Cramer, Helen
Abstract: Background: Studies have shown variation in care for patients with non‐ST elevation myocardial infarction (NSTEMI), including in the roles of specialist and advanced practice nurses in diagnosis, treatment and coordination of care. Aim: The aim of this study was to describe the roles and responsibilities of specialist and advanced practice nurses in providing care for patients with NSTEMI. Methods: Secondary analysis of observational field notes and interviews from an ethnographic study of variation in care for NSTEMI patients in 10 UK hospitals conducted 2011–2012. Data were thematically analysed to identify key concepts and themes related to the roles of specialist nurses. Results: Seven of 10 hospitals had roles for specialist nurses in NSTEMI care. The major theme related to high demand and the complexity of patients and organizations ('Aligning the planets'). In this theme, nurses contributed to improving services or compensating for deficiencies ('Making the system work versus making up for the system'). Data collection for audit could take precedence over time with patients ('Paying worship to the paper'). Nurses expressed a sense of ownership of cardiovascular patients that drove their desire to provide quality of care ('They are our patients').